2015
DOI: 10.1007/s00464-015-4101-5
|View full text |Cite
|
Sign up to set email alerts
|

Robotic approach improves spleen-preserving rate and shortens postoperative hospital stay of laparoscopic distal pancreatectomy: a matched cohort study

Abstract: RA-LDP was associated with a significantly better SP rate and reduced OT, blood loss, transfusion requirement, and PHS for patients undergoing SP compared to C-LDP, but offered less benefits for patients undergoing splenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
115
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(133 citation statements)
references
References 32 publications
14
115
4
Order By: Relevance
“…(42) Hence, based on the current evidence, we can only conclude that RDP is feasible and can be performed safely. (7,11,17) However, there is also growing evidence suggesting that RDP may be associated with a shorter learning curve, (15) a lower conversion rate (15) and an increased rate of splenic preservation (11,23,34,38,42) as compared to conventional laparoscopy. In a recent study by Kang et al from Yonsei University, Korea, the authors reported that the rate of splenic preservation was demonstrated a distended bowel with no transition point.…”
Section: Casementioning
confidence: 90%
See 1 more Smart Citation
“…(42) Hence, based on the current evidence, we can only conclude that RDP is feasible and can be performed safely. (7,11,17) However, there is also growing evidence suggesting that RDP may be associated with a shorter learning curve, (15) a lower conversion rate (15) and an increased rate of splenic preservation (11,23,34,38,42) as compared to conventional laparoscopy. In a recent study by Kang et al from Yonsei University, Korea, the authors reported that the rate of splenic preservation was demonstrated a distended bowel with no transition point.…”
Section: Casementioning
confidence: 90%
“…(18) Although there has since been a growing number of RDP cases, the number of case series involving more than 15 patients that report on the outcome of RDP is limited (Table II). (11,17,(37)(38)(39)(40)(41)(42) The published case series are also limited to centres located in Italy, the United States, China and Korea. The first spleen-saving RDP in Korea was only reported recently in 2011.…”
Section: Casementioning
confidence: 99%
“…Moreover, the risk of developing gastric or esophageal varices and potential varices bleeding due to a portal hypertension is reduced by preserving the splenic vein [2,[9][10][11] . Since several authors reported serious problems like splenic infarctions or abscesses after the Warshaw procedure [12,13] , it is supposed that vessel-preserving spleen-preservation (SP) in DP is beneficial for patients with benign and borderline tumors [11,14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…In spleen preserving techniques where pancreatic branches from the splenic vein and artery are individually ligated and sutured (splenic vessel preservation), robotic surgical systems increase the likelihood of successful splenic preservation compared to traditional laparoscopy (2,3). This effect can be explained by the impact of the robotic instrument articulation providing greater needle dexterity which is critical in ligating small venous or arterial branches along the relatively thin-walled splenic vein.…”
Section: Rationalementioning
confidence: 99%
“…A majority of surgeons had utilized laparoscopic techniques for minimally invasive distal pancreatectomy prior to the advent of modern robotic surgical systems. In contrast to traditional laparoscopy, robotic distal pancreatectomy has been shown to be feasible in performing both standard and more complex resections with greater technical demands (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%